Impact of pH on the high-pressure inactivation of microbial transglutaminase - Queirós, Rui P. (2018)
Microbial transglutaminase (MTG) is an enzyme largely used in the food industry, mainly to improve food texture. However, many globular proteins show low susceptibility to the action of this enzyme. High-pressure processing (HPP), being able to change protein conformation, may be a useful tool to increase the accessibility of globular proteins to the action of MTG. Nevertheless, HPP conditions need to be carefully optimized to avoid the expected decrease of enzymatic activity observed above certain conditions of pressure (P), treatment time (t) or temperature (T). Pressure inactivation of MTG under different HPP conditions (200–600 MPa; 20–40 °C; 10–30 min) was evaluated employing a face-centered composite design at four different pH values (4–7). The regression models obtained presented high coefficients of determination and high F values, although they could not explain some of the associated variability. At all the pH values tested, the three main factors (P, T, and t) significantly (p < 0.05) affected the activity of MTG. At least 20% of MTG was inactivated when low pressures (200 MPa) were used at pH 4 and 5, whereas a higher pressure above 400 MPa was needed to obtain a similar inactivation at pH 6 or 7. MTG pressure-inactivation followed first-order kinetics under all tested conditions. Inactivation rate constants decreased with increasing pressure at constant temperature and pH 4, with a positive activation volume (Va), while the opposite was verified for the other pH values. Both activation energy (Ea) and Va were dependent on pH, however, at the lower pH values, Ea and Va did not vary significantly with pressure and temperature, respectively. Overall, MTG can be considered relatively resistant to pressure, particularly near its optimal pH.